Comparing Student Nurses’ Satisfaction with OSCE and Traditional Clinical Skill Assessment Methods - Rincy T. Issac; Jose, Julia; Jose, Jency; Kunjumon, Neethu (Innovations in Pedagogy and Technology, 2026)
Assessment of clinical skills is a crucial aspect of nursing education, ensuring that students acquire the necessary competencies to provide high-quality patient care. The Objective Structured Clinical Examination (OSCE) and the Traditional Method of Clinical Skill Assessment (TMCSA) are two commonly used approaches. This study aimed to compare student nurses’ satisfaction levels with OSCE and TMCSA. A descriptive comparative study was conducted among 70 BSc Nursing students at a selected college of nursing. Data collection was performed using an observation checklist for cardiac assessment and a satisfaction rating scale. The data were analysed using mean, standard deviation, and t-test to compare satisfaction levels between OSCE and TMCSA. The study findings showed that 90% of student nurses were satisfied with TMCSA, whereas only 42.9% expressed satisfaction with OSCE. Statistical analysis indicated a significant difference in satisfaction levels (t = 6.845, p = 0.000), favouring TMCSA. The findings suggest that while OSCE is a structured and standardized assessment method, students perceive TMCSA as more favourable. This study highlights the need for a balanced approach to clinical assessment methods by integrating both traditional and modern evaluation techniques in nursing education. Such an approach not only enhances student satisfaction and clinical competence but also holds significant implications for pedagogy and innovation-encouraging educators to adopt more evidenced-based, student-centered and technologically enhanced assessment strategies that foster deeper learning and reflective practice.